2019
DOI: 10.5005/jp-journals-10005-1594
|View full text |Cite
|
Sign up to set email alerts
|

Epidermoid Cyst of the Tongue—A Rare Case

Abstract: Introduction Epidermoid cysts are commonly found in various part of the body, but its occurrence in the oral cavity is relatively rare. Case presentation Present case highlights the importance of involvement of epidermoid cyst within the tongue in 10-year-old child. Discussion The occurrence of epidermoid cyst within the tongue is an extremely rare phenomenon and only few cases have been reported in the literature. Clinically they are painles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…EC is a rare injury in the oral cavity 7,10 , and it is even much rarer in the tongue 2,7,10 . 2018) performed a literature review with the published cases of EC in the tongue and found just 12 cases of EC, plus the case they were reporting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…EC is a rare injury in the oral cavity 7,10 , and it is even much rarer in the tongue 2,7,10 . 2018) performed a literature review with the published cases of EC in the tongue and found just 12 cases of EC, plus the case they were reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment involves enucleation, and it may be performed intra-or extraorally, with low recurrence rates [3][4][5] . In addition to that, few cases have been reported in the literature, especially those affecting the tongue 7 . The tongue is a structure that is difficult to evaluate 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations